Location-Based Application for Reporting Sexual Violence - Wahyudi, Rian Tri; Wahyuni, Elyza Gustri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Sexual violence is a significant and increasing issue in Indonesia, with severe impacts on the physical health, psychological well-being, and overall welfare of victims. On campuses, these incidents often remain unreported due to factors such as shame, fear, and the absence of secure reporting mechanisms. Universitas Islam Indonesia (UII) has established a Task Force for the Prevention and Handling of Sexual Violence (PPKS) and implemented specific regulations to address these issues. This research aims to develop a location-based reporting application for sexual violence incidents within the UII campus. The Android application utilizes technologies such as Global Positioning System (GPS), Google Maps API, Geolocation API, and Firebase to enable real-time incident reporting. Users can report incidents by providing identification, location data, and video evidence, which supports investigations by the PPKS Task Force at UII. The results demonstrate that the application is effective as a reporting medium for sexual violence on campus. The integration of GPS, Google Maps API, and Geolocation API facilitates efficient geographic positioning, while Firebase is employed as a backend solution for secure and organized data storage and management, allowing rapid access by the PPKS Task Force. This application enables the PPKS Task Force to monitor and respond to reports promptly, enhancing the safety and confidence of victims. Therefore, the application is anticipated to become an essential tool in the prevention and management of sexual violence at UII.